Rozdział 1. Wyrwać człowieka ze świata absurdu. O zadaniach filozofii wobec wyzwań nihilizmu i autodestrukcji - Robaczewski, Arkadiusz (The phenomenon of euthanasia: Philosophy – Culture – Medicine – Law, 2025)
The chapter shows how changes in the understanding of man and his nature led to the emergence of the phenomenon of nihilism, against the background of which hedonism was born, leading to a sense of meaninglessness of life and, as a result, to euthanasia. Euthanasia is a consequence of the hedonism of modern societies. It takes various forms: from primitive consumerism, satiation of the senses, to more sophisticated practices of self-realization, but it has one root – a lack of respect for human nature, which set a transcendent goal for man. A well-functioning reason interprets the real world and tries to reconcile its own actions with it, while in the case of a reason devoid of integrity, a perverted re-ason, we are dealing with the adaptation (or rather, its attempt) of the real world to man’s desires. By “love” (“help”), therefore, the euthanasia advocate means a set of subjective desires that do not reckon with the real world. Modern man is afraid of what is real. He is afraid to such an extent that he is not in control of everything, that he does not have power over everything, that, escaping from reality and from death, he is ready to commit suicide.